2011
DOI: 10.1002/pmic.201000745
|View full text |Cite
|
Sign up to set email alerts
|

Proteome characterization of sea star coelomocytes – The innate immune effector cells of echinoderms

Abstract: Sea star coelomic fluid is in contact with all internal organs, carrying signaling molecules and a large population of circulating cells, the coelomocytes. These cells, also known as echinoderm blood cells, are responsible for the innate immune responses and are also known to have an important role in the first stage of regeneration, i.e. wound closure, necessary to prevent disruption of the body fluid balance and to limit the invasion of pathogens. This study focuses on the proteome characterization of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Interestingly, almost all these proteins were found in other mucus proteomes (see supplemental Table S4). In echinoderms, two types of immune response have been described: a cellular response, mediated by coelomocytes, circulatory cells present in the perivisceral coelomic cavities, and a humoral response mediated by molecules present in the coelomic fluid [87,88]. Several of the immune cells-related proteins highlighted in this study were also found in sea urchin tube foot proteome [89].…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…Interestingly, almost all these proteins were found in other mucus proteomes (see supplemental Table S4). In echinoderms, two types of immune response have been described: a cellular response, mediated by coelomocytes, circulatory cells present in the perivisceral coelomic cavities, and a humoral response mediated by molecules present in the coelomic fluid [87,88]. Several of the immune cells-related proteins highlighted in this study were also found in sea urchin tube foot proteome [89].…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…In the starfish Asterias rubens, Gorshkov and collaborators (2009) (15) detected two types of cells that were named just mature and immature coelomocytes. In our model starfish M. glacialis, Franco (2011) (16), using light microscopy, reported four types of coelomocytes: spherule cells, vibratile cells, amoebocytes and phagocytes (the latter showing petaloid or filopodial alternate morphologies). Giving this range and diversity of morphologies, it is nowadays unanimously accepted that the types and characteristics of coelomocytes vary among the five echinoderms classes (3).…”
Section: Introductionmentioning
confidence: 89%
“…The subsequent gel images were exported into Progenesis SameSpots and matched to the images generated from previous analysis. All spots showing a phosphoprotein signal either in controls and in injured animal groups or, showing a significant change in the relative amount of protein phosphorylation, were manually excised from the four 2DE gel technical replicates and pooled for posterior in‐gel digestion . Briefly, modified trypsin (6.7 ng/μL in 50 mM ammonium bicarbonate) was added to the dried gel plugs and incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The latter are more likely to be extended to mammals than those observed in other classical regeneration models phylogenetically more distant from chordates. Nowadays, the intriguing question of how echinoderms deploy and regulate their regenerative capabilities remains unknown, however several studies either using transcriptomics , individual gene candidates , or proteomics started to clarify this complex biological event. For instance, at present nothing is known on how protein PTMs, such as phosphorylation, are tailoring echinoderm intrinsic neuronal growth aptitudes.…”
Section: Introductionmentioning
confidence: 99%